Comparative Formaldehyde Content in Some Fresh and Ice-packed Fishes Available in Imphal Market, Manipur - Bishwarup, Konjengbam; Sarojnalini, Chungkham (Asian Journal of Biological and Life Sciences, 2024)
Quantitative determination of formaldehyde in three species of fresh and ice-packed fishes namely Labeo rohita (Hamilton, 1822), Pangasius pangasius (Hamilton, 1822) and Piaractus brachypomus (Cuvier, 1818) were conducted. The study observed different concentrations of formaldehyde in different body regions of all the studied ice-packed fishes. Among fresh fishes, formaldehyde was detected only in P. brachypomus. In the ice-packed fishes, formaldehyde concentrations were found in the range of 0.80-1.19 μg/g in L. rohita, 1.23-1.39 μg/g in P. pangasius and 0.86-1.15 μg/g in P. brachypomus. The results indicated that there was additional formaldehyde in those icepacked fishes. Since, formaldehyde is carcinogenic, it will likely cause human health hazards. So, it must be avoided for use in preservation and storage of foods including fishes. The study showed that fresh fishes were better and safer than ice-packed fishes for human health.
Keywords: Carcinogenic; Formaldehyde; Fresh; Ice-packed